Effect of education on cognitive performance in patients with mild cognitive impairment - Godinho, Filipe (2022)
This study aims to investigate if education (as a cognitive reserve proxy) modifies the profile of cognitive performance. We hypothesize that participants with higher education can remain functional (due to a better executive performance), despite a more severe memory impairment, compared with lower education individuals. One hundred and sixty-six mild cognitive impairment (MCI) individuals with at least one comprehensive neuropsychological evaluation were included in a retrospective, cross-sectional study and divided into two groups (Low Education—LE [1–4 years] and Medium-to-High Education—MHE [> 4 years]). A total of 22 neuropsychological measures were analyzed. Age-adjusted results were subject to simple regression analyses to determine the variance explained by education. Average scores and proportions of low performances were subject to group comparison. The results showed similar cognitive decline patterns between individuals with LE and MHE, with no significant difference in each cognitive domain. However, MHE revealed a steeper decline in certain cognitive domains, such as sustained attention and episodic memory, compared with the LE. Moreover, MHE showed a trend to higher proportion of tests affected when compared to LE. These suggest that individuals with higher education may remain in a MCI stage despite a more widespread cognitive impairment, reflecting a higher cognitive reserve.